Sosialisasi Alat Peraga Matematika Akar Pangkat Tiga di SD Negeri Kedai Runding - Faizin Faizin (Institut Teknologi dan Bisnis Semarang, 2023)
This service was motivated by the existence of problems among students at SD Negeri Kedai Runding Class V, namely that some students had difficulty solving mathematics problems and their learning outcomes were still low. Drawing cube roots is usually quite difficult material for elementary school children. This happens because the teacher only uses the prime factorization method in learning, not encouraging students to actively participate in learning. To overcome this, PAPA ANGGA is used because by using PAPA ANGGA students can be actively involved and can help students who have learning difficulties. The approach or method that I use in this socialization is Participatory Action Research (PAR) which is a research approach that involves active participation from community groups who are research subjects. This method aims to produce knowledge that is relevant, useful, and can be applied in everyday life. day. This activity was carried out at SD Negeri Kedai Runding Class V. With the PAPA ANGGA mathematics teaching aids which contain cube roots, students can easily understand and solve cube roots using props.